The Moore Penrose Inverse of Interval valued Neutrosophic Fuzzy Matrices - Mageswari V. (Mathematical Statistician and Engineering Applications, 2022)
This work presents a method to discover the g-inverse of interval valued Neutrosophic intuitionistic fuzzy matrix's (IVNFM). Additionally, the concept of an interval valued intuitionistic fuzzy vector's standard basis is presented. A few findings about the g-inverse of IVNFM are examined.